Contabilidade macroeconômica dos Recursos Hídricos: uma abordagem insumo-produto aplicada à economia do estado do Ceará, Brasil - Soares, Rogério Barbosa (2023)
This work aimed to broaden the discussion on the use of principles and models economics in the planning and management of water resources in semi-arid regions. For that, four studies were elaborated, they are: i. Estimation of Direct and Indirect Consumption of Resources Hydro: An Input-Output Analysis; ii. Macroeconomic Resource Accounting Water Resources: An Input-Output Approach to Linkages and Impacts on the Economy of Ceará State, Brazil; iii. Spatial Analysis of the Water Demand of the Economic Sectors of the State of Ceará and iv. Evaluation of Virtual Water Flows between Macroeconomic Sectors from Ceará. In the first, the direct and indirect consumption of water in the state of Ceará was mapped, from sectoral and intersectoral way, measuring the economic benefits of its use through the construction of the Water Resources Input-Output Matrix (MIPRH) for the year 2013, considering 32 sectors and 58 products. This identified that the direct consumption of water by economic sectors was 1.33 trillion m³, with agriculture accounting for 62.08% (826,740,891m³), services accounting for 30.50% (406,129,808m³) and industry for 7.42% (98,816,204m³). These generated an economic return for the use of water of: R$8.04/m³, R$573.94/m³ and R$249.89/m³, respectively. As for the intersectoral indirect consumption of water resources, this was 193,471,666m³. The second study identified the main sectors of the economic structure, considering their virtual water flows, and estimated the impact of each sector, highlighting systemic characteristics of the water demand of the economic sectors in the regional economy based on Ceará's MIPRH. For this, we used: the indices Rasmussen and Hirschman for the "back and forth links"; general multipliers of production, work and income; and the elasticity of water consumption to final water demand. This study found that: (a) the commercial sector is the most relevant in terms of connections back and forth of virtual water flows, (b) the agricultural sector has the highest consumption direct water consumption, and (c) the public administration sector has the highest intermediate water consumption water. The third study evaluated the spatial dependence of total water consumption through the Exploratory Analysis of Spatial Data (AEDE), using the statistical tests of Spatial Autocorrelation: Global Moran Index (I) and the Local Indicator of Association (LISA), working with a univariate spatial model to identify the degree of spatial association of total water consumption and with a bivariate model to identify the spatial association between total water consumption and Gross Added Value of each municipality in the state of Ceará. Based on statistical analysis of the Global I-Moran Index, it was found that there are municipalities that have a positive spatial autocorrelation. In the analysis univariate by the Local Indicators of Spatial Association (LISA), we identified the existence Clusters of municipalities with Upper-High aggregation in the Lower River Basin Jaguaribe, Curu, Coast, Middle Jaguaribe and Metropolitan Basins. In the bivariate analysis, the High-High Local Indicators pattern comprised municipalities in Ceará located in the Hydrographic Regions of Acaraú, Banabuiú, Baixo Jaguaribe, Litoral, Médio Jaguaribe and Metropolitan Basins Region. The fourth study identified and evaluated how the flows of virtual water are taking place through trade in goods and services between municipalities and hydrographic regions of Ceará, with the application of a complex network algorithm - Model Multiregional Analysis of Inputs-Outputs, for the identification and evaluation of the flows of virtual water, combined Theory of Networks, structural analysis of the economy of the state of Ceará (MIPRH – Ceará) and spatial econometric models. The results obtained show that: 1) The hydrographic region of the Metropolitan Basins concentrates 73.0% of the outflows of virtual water and 72.3% of input flows, generated through water transfers via intra and inter regional commercial transactions in Ceará; 2) the economic activities that export a greater volume of virtual water flows are: Livestock, including support services to livestock; Wholesale and retail trade, except motor vehicles; forest production, fisheries and aquaculture and Slaughter and meat products, including dairy and fisheries products, 3) the municipalities of Fortaleza (179,891,952 m³), Maracanaú (35,842,056 m³) and Aquiraz (25,397,696 m³), were the ones with the highest volume of virtual water output, 4) the econometric models showed that positive variations in the level of production of sectors economic: agriculture, industry and services result in positive variations in consumption economic use of water in the municipalities of the state of Ceará. 5) The Spatial Lag Model (MDE) indicates that by raising the GVA of Agriculture by 10% the total water consumption increases by 7.3%, and if there is a 10% increase in the Industry GVA, the MDE model predicts a increase of around 7.2% in total water consumption. On the other hand, a 10% increase in Services GVA results in an increase estimate of the total water consumption of the order of 1%. Thus, based on the proposed studies, it was found that the use of Environmental Macroeconomic Accounting for Water can support the development of public policies aimed at the planning and management of water resources, addressing connections between economic growth policy objectives and water security regional, performing the integration of information related to the use of water as an asset with economic information related to the productive structure of each sector macroeconomic.